Hedonic Value and Attitude Toward Purchase Intention Among Generation Y and Z - Maulidaninta Queen Nayla; Binarin Tirto Andika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the factors influencing purchase intention by examining the roles of attitude, perceived behavioral control (PBC), perceived hedonic value (PHV), perceived utilitarian value (PUV), and subjective norm (SN). The research employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test both the measurement model (outer model) and the structural model (inner model). Data were collected via survey and analyzed through convergent and discriminant validity assessments, reliability tests, collinearity diagnostics, and hypothesis testing using t-statistics and p-values. Results indicate that all constructs exhibit adequate validity and reliability, with outer loading values exceeding 0.70 and the highest AVE observed in the SN construct (0.724). The R-square for purchase intention is 0.953, indicating that the model robustly explains the variability in purchase intention. Hypotheses were supported for the influence of PUV on attitude (t=3.537; p=0.000), PHV on attitude (t=9.664; p=0.000), PHV on purchase intention (t=47.893; p=0.000), and attitude on purchase intention (t=6.366; p=0.000). However, the direct effects of PUV, SN, and PBC on purchase intention were not statistically significant. These findings underscore the pivotal role of hedonic value and consumer attitude in shaping purchase intention, offering practical implications for marketing strategies that emphasize emotional appeal and consumer perception.